(untitled) (Journal of Guidance and Counselling Studies, 2024)
Using correlational research design, this study sought to establish the relationship betweenpsychological capital and academic engagement of in-school adolescents in Anambra State. Two research questions and two null hypotheses guided the study. The population of the study consisted of all the 12, 172 Senior Secondary School (SS2) students in the 263 public secondary schools in Anambra State. The sample for the study consisted of 750 SS2 students drawn from the population of the study using multi-stage random sampling technique. Two sets of questionnaire ‘Psychological Capital Questionnaire (PCQ) and ‘Academic Engagement Questionnaire (AEQ)’ were used for data collection. The instruments for data collection were validated by 3 specialists in Education (2 from Educational Psychology and 1 from Measurement and Evaluation). The reliability of the instruments was established using Cronbach Alpha Method and the alpha co-efficient got were 0.78 for PCQ and 0.82 for AEQ.Data collected were analyzed using Pearson Product Moment Correlation and Coefficient of Determination for answering the research questions while regression statistical analysis was used for testing the hypotheses. The findings of the study revealed that gender notwithstanding, there is a high positive relationship between self-efficacy and academic engagement of in-school adolescents in Anambra state. Also correlation between optimism and academic engagement of in-school adolescents in Anambra state varies with gender. Based on the findings of the study, it was recommended among others that Government should prioritise teachers’ welfare to engender their zeal and passion so as to ignite the needed psychological capital in the students, thus positively impacting their academic engagement.